THE ROLE OF GOOD CORPORATE GOVERNANCE (GCG) IN MAXIMIZING THE FINANCIAL PERFORMANCE OF ISLAMIC BANKING IN INDONESIA - Toufan Aldian Syah (DAS Institute, 2021)
The growth in the financial performance of Islamic banking in Indonesia is still an exciting discourse to discuss. This is because Indonesia, which is a Muslim country with the largest market share of halal products in the world, does not yet have a Sharia financial industry whose performance is classified as useful. The research attempts to explain how the principles of good corporate governance with the addition of Islamic principles can be a solution for the development of Islamic banking performance. The research method uses a qualitative approach and literature study. The results obtained from this study are that good corporate governance is expected to improve the company's financial performance in terms of managing company fixed assets, utilizing human resources, utilizing financial capital and maximizing corporate structure.